Distribución y abundancia de equinodermos en las aguas someras de la Isla del Coco, Costa Rica (Pacífico Oriental) - Alvarado, Juan José; Chiriboga, Ángel (Revista de Biología Tropical, 2008)
Distribution and abundance of shallow water echinoderms from Cocos Island, Costa Rica, Eastern Pacific. The distribution patterns of the shallow water echinoderms (down to 18 m deep) around Isla del Coco, Costa Rica, are described. Eighteen sites were evaluated at two depths (6 and 15 m) using transects, and vertical profiles were done between 0 and 18 m deep at four sites. A total of 28 species were observed. The most specious class was Echinoidea with nine species, followed by Asteroidea with seven, and Ophiuroidea and Holothuroidea with six species each. The sea urchin Diadema mexicanum was the only echinoderm present at all sites and depths studied. The highest densities were observed at Dos Amigos at 6 m (6.53 indv/m2), Punta Ulloa (4.37 indv/m2), Roca Sumergida (3.48 indv/m2) and Isla Pájara (2.27 indv/m2). Diadema has shown in the past to be an important element in the balance and recovery of the coral environments. This study reports for the first time the presence in the area of the asteroid Asteropsis carinifera and the sea cucumber Holothuria (Mertensiothuria) fuscocinerea. Rev. Biol. Trop. 56 (Suppl. 2): 99-111. Epub 2008 August 29.